2008
DOI: 10.1016/j.psychres.2006.01.022
|View full text |Cite
|
Sign up to set email alerts
|

IQ decline in cross-sectional studies of schizophrenia: Methodology and interpretation

Abstract: Some researchers have compared neuropsychological performance in schizophrenia groups with and without presumed IQ decline. Inherent in this approach is an assumption that group differences are due to different IQ trajectories (stable vs. declining), but neuropsychological differences could be a function of current IQ regardless of the presence or absence of previous IQ decline. We examined this issue in 93 normal controls and in 80 patients classified as having preserved (27.5%), deteriorated (50%), or compro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
47
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 49 publications
6
47
2
Order By: Relevance
“…Our cannabis-using patients also had a smaller difference between current IQ and premorbid IQ than non-using patients. Kremen et al (2008) point out that premorbid estimates should be understood as a measure of "potential" had a given subject not been destined to develop schizophrenia. Thus, individuals with a high premorbid IQ could be seen as less predisposed.…”
Section: Discussionmentioning
confidence: 99%
“…Our cannabis-using patients also had a smaller difference between current IQ and premorbid IQ than non-using patients. Kremen et al (2008) point out that premorbid estimates should be understood as a measure of "potential" had a given subject not been destined to develop schizophrenia. Thus, individuals with a high premorbid IQ could be seen as less predisposed.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, recent population-based estimates of intellectual deterioration indicate rates as high as 98% for patients with schizophrenia, who show measurable decline in intellect from premorbid levels (Keefe et al, 2005). Typically, studies use a psychometric index of intellectual deterioration computed on the basis of IQ-oral reading difference scores (e.g., Kremen et al, 2008;Weickert et al, 2000). Oral reading is considered a reliable and valid proxy estimate of premorbid intelligence, because it is both highly correlated with IQ and preserved in a variety of adult onset cognitive disorders.…”
mentioning
confidence: 99%
“…Studies of schizophrenia using this index have reliably classified patients as having preserved, compromised, or deteriorated IQ (Badcock et al, 2005;Kremen et al, 2008;Weickert et al, 2000). For example, Kremen et al (2008) recently classified 80 patients as either intellectually deteriorated (50%) with subaverage IQ but normative oral reading, intellectually compromised (22.5%) with similarly subaverage IQ and oral reading, or intellectually preserved (27.5%) with average or above IQ and oral reading.…”
mentioning
confidence: 99%
“…The Wechsler Adult Intelligence Scale (WAIS) has been used exten sively to assess cognitive functions in patients with schizophrenia for both research and clinical practices [3,[13][14][15][16][17][18]. The Wechsler Adult Intelligence Scale-III (WAIS-III) has been updated from the Wechsler Adult Intelligence Scale-Revised (WAIS-R).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that patients with schizophrenia tend to have higher VIQ than PIQ [18,23]. In a study with 42 participants diagnosed with schizophrenia, the average IQ scores were in the low average range, indicating a decline in performance compared to the general population [20].…”
Section: Introductionmentioning
confidence: 99%